Classic kaposi sarcoma with pulmonary involvement mimicking endobronchial tuberculosis in a child1. Issue 3 (23rd July 2012) - Cakir, Fatma B.; Cakir, Erkan; Tuzuner, Nukhet; Kut, Arif
Abstract Kaposi' sarcoma (KS) is a low‐grade vascular neoplasm and classic KS, a subtype of KS, is extremely rare in children. Childhood pulmonary involvement in classic KS has not been reported in the literature. We describe an HIV‐seronegative pediatric case with a fulminant course of classic KS with pulmonary involvement mimicking endobronchial tuberculosis. Pediatr Pulmonol. 2013; 48:310–312. © 2012 Wiley Periodicals, Inc.